ANALISIS PENGARUH KEPERCAYAAN, RELIGIUSITAS DAN KONTRIBUSI TERHADAP MINAT PEDAGANG DI PASAR LOS KOTA LHOKSEUMAWE MENGELUARKAN ZAKAT DI BAITUL MAL - Muhammad Yunus; Mulkan Syahriza (AL-ILMU, 2022)
The purpose of this study was to analyze the influence of belief, religiosity and contribution to the interest of traders in the Los Market in Lhokseumawe City to issue zakat in Baitul Mal. The object of the research is the traders with the sampling technique using the simple sample random sampling method (sample random sampling). The sample is 69 traders. Collecting data using a questionnaire. The data analysis technique used a qualitative and quantitative descriptive analysis approach with multiple linear regression. The measurement uses a Likert scale with a range of answers from 1 to 5. From the results of data processing using a regression model, it is found that Y = 4.295 + 0.406X1 – 0.261X2 + 0.645X3. While the partial test results on the influence of the belief factor (X1) significantly amounted to 4,988, greater than the t table value of 1,997 at = 5%, the influence of the religiosity factor (X2) of -2,733, greater than the t table value of 1,997 in = 5% and the influence of the contribution factor (X3) is 7,738, greater than the t table value, which is 1,997 at = 5%. This means that partially trust, religiosity and contribution factors have a positive effect on interest in paying zakat in Baitul Mal. Each independent variable has a t-count value greater than t-table at a significance of = 5%. Simultaneous testing of trust, religiosity and contribution factors to the effect of paying zakat in Baitul Mal conducted by Lhokseumawe City Los Market traders obtained the F count of 132.278 and F table 3.14. Shows if the calculated F is greater than the F table using an interest rate of 95%, = 5% (0.05). The results of these data indicate that there is a significant effect simultaneously, so the hypothesis ho is rejected. From this study it was concluded that there was an influence of trust, religiosity and contribution factors partially and simultaneously on the effect of paying zakat in Baitul Mal carried out by traders at the Los City Market, Lhokseumawe.